Ecological Isolation Maintains the Species Boundaries Between Two Sympatric Cycas From Southwest China - Fanggui Zheng; Yiqing Wang; Huihui Xi; Siyue Xiao; Xiuyan Feng; Xun Gong; Jian Liu (Ecology and Evolution)
ABSTRACT Over long‐term evolutionary processes, sympatric affinities may develop reproductive isolation mechanisms, such as temporal isolation and ecological divergence, to maintain species independence. However, due to lacking strict geographic isolation barriers, sympatrically distributed closely related species may experience interspecific gene flow and genetic introgression, which can blur species boundaries. Here we focus on two sympatrically distributed Cycas species along the Lancang (Mekong) River in three populations from Southwest China, Cycas pectinata and C. simplicipinna, to investigate the extent of genetic introgression between them and how they maintain species boundaries. Using 16 microsatellite markers, we first genotyped and assessed the introgression patterns between the two species and their seedlings in each population. We further compared their geographical and ecological divergence, including the fine‐scale spatial distribution, habitats, reproductive phenology, and pollinators, based on a systematic field survey across its entire range in China. We found that sympatric populations of C. pectinata and C. simplicipinna, along with their seedlings, showed no genetic admixture. Further evidence supports that the two species exhibited significant variations in habitat indicators such as slope position and soil pH. Additionally, significant differences were observed in pollinator communities and coning behavior. These findings indicate that there is no hybridization between C. pectinata and C. simplicipinna under natural conditions. Instead, they maintain species boundaries primarily through reproductive isolation driven by divergent coning times and pollinator specificity, coupled with niche differentiation. This study not only provides a representative case for understanding mechanisms of plant species boundary maintenance but also offers critical theoretical support for the reintroduction and conservation of cycads.